2013
DOI: 10.3109/00016357.2013.795659
|View full text |Cite
|
Sign up to set email alerts
|

Salivary biomarkers: Relationship between oxidative stress and alveolar bone loss in chronic periodontitis

Abstract: Important oxidative stress associated with alveolar bone loss biomarkers can be detected in saliva of patients with periodontal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
142
3
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(175 citation statements)
references
References 38 publications
25
142
3
5
Order By: Relevance
“…In our studies salivary levels of uric acid were signifi cantly decreased in chronic periodontitis patients as compared to controls. At the same time uric acid was found in a negative correlation with CTX I and MMP-8 both markers of bone resorption [ 55 ]. This fi nding shows that saliva refl ects the associations that can exist between decreased concentrations of antioxidant mechanisms and development of periodontal disease.…”
Section: Saliva: Antioxidant Defense Systems and Oxidative Stress Biomentioning
confidence: 52%
See 1 more Smart Citation
“…In our studies salivary levels of uric acid were signifi cantly decreased in chronic periodontitis patients as compared to controls. At the same time uric acid was found in a negative correlation with CTX I and MMP-8 both markers of bone resorption [ 55 ]. This fi nding shows that saliva refl ects the associations that can exist between decreased concentrations of antioxidant mechanisms and development of periodontal disease.…”
Section: Saliva: Antioxidant Defense Systems and Oxidative Stress Biomentioning
confidence: 52%
“…TAC is signifi cantly decreased in smokers, patients with periodontal affections, patients with oral cancer or diabetes. In a recent study our group demonstrated that saliva from chronic periodontitis patients had a decreased TAC value compared to normal controls [ 55 ]. However, TAC did not correlate with other analyzed periodontal biomarkers.…”
Section: Saliva: Antioxidant Defense Systems and Oxidative Stress Biomentioning
confidence: 99%
“…A correlation between salivary MDA levels and C-terminal telopeptide of type I collagen, a biomarker for bone loss, was also reported. 46 These findings point to a possible systemic low AO expression in CP, but the relative contribution of oPMNs to low oral AO capacity may be critical for disease progression.…”
Section: Nrf2 Down-regulation In Periodontitismentioning
confidence: 93%
“…Miricescu et al analyzed the relationship between oxidative stress and alveolar bone loss in chronic periodontitis (32). Significant positive correlations were observed between osteocalcin and clinical parameters of periodontal disease.…”
Section: Markers Of Alveolar Bone Lossmentioning
confidence: 99%